2018
DOI: 10.1016/j.bja.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the effects of intensive-care-unit noise on sleep of healthy subjects and the critically ill

Abstract: Intensive-care-unit (ICU) patients exhibit disturbed sleeping patterns, often attributed to environmental noise, although the relative contribution of noise compared to other potentially disrupting factors is often debated. We therefore systematically reviewed studies of the effects of ICU noise on the quality of sleep to determine to what extent noise explains the observed sleep disruption, using the Cochrane Collaboration method for non-randomized studies. Searches in Scopus, PubMed, Embase, CINAHL, Web of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 44 publications
(34 reference statements)
1
29
0
18
Order By: Relevance
“…The sound measurement results of the current study show that our ICU may not be as noisy as other ICUs reported in past publications (Horsten et al, ). There are several potential reasons for this.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The sound measurement results of the current study show that our ICU may not be as noisy as other ICUs reported in past publications (Horsten et al, ). There are several potential reasons for this.…”
Section: Discussionsupporting
confidence: 60%
“…However, noise has only indirectly been linked to sleep disruption in ICU patients, and the differences between patients are not well understood (Aaron et al, 1996;Freedman et al, 1999;Gabor et al, 2003;Xie et al, 2009). Furthermore, these patient studies were hampered by small sample sizes, low quality of evidence and high risks of bias, further limiting the generalizability of their results (Horsten, Reinke, Absalom, & Tulleken, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Intensive care units are particularly noisy areas of hospitals . Neonatal units have average sound pressure levels of 48–61 dB for up to 95% of the time , paediatric units average 53–73 dB and adult units are 53–59 dB . The unit at the John Radcliffe Hospital when measured in 2012 had daytime averages of 58 dB at the desk and 60 dB adjacent to the patient .…”
Section: Discussionmentioning
confidence: 99%
“…Excessive noise in ICUs disrupts patients’ sleep , increases sleep medication use , sedation use and the incidence of delirium . Ambient sound markedly reduces the intelligibility of speech in acute care areas , which can contribute to avoidable errors in care.…”
Section: Discussionmentioning
confidence: 99%
“…Pesquisas (YAO et al, 2008;CEOLIM, 2013;HORSTEN et al, 2018) nesse sentido buscam o entendimento de fatores que afetam positivamente ou negativamente na qualidade do sono de indivíduos, destacando-se: a iluminação intensa, ocorrência de ruídos e movimentação durante o período noturno. Assim, as informações básicas abordadas neste estudo são: i.)…”
Section: Sistema De Monitoramento Do Ambiente -Qualidade Do Ambiente unclassified